2010
DOI: 10.1111/j.1471-4159.2010.06688.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome deficiency alters retinal proteasome’s response to stress

Abstract: Abbreviations used: BCA, bicinchoninic acid; IjB, inhibitor of NFjB; KO, L7, lmp7 )/) ; L7M1, lmp7 )/) mecl-1 )/) ; NFjB, nuclear factor jB; PA, proteasome activator; RPE, retinal pigment epithelium; WT, wild-type. AbstractOur previous work demonstrated that immunoproteasome is up-regulated in the retina and brain in response to injury that does not involve an inflammatory response (J. Neurochem. 2008; 106:158).These results suggest additional non-immune functions for the immunoproteasome in the cellular str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 45 publications
12
99
0
Order By: Relevance
“…jci.org Volume 125 Number 5 May 2015 oxidized proteins. All 3 immunoproteasome-specific subunits are upregulated under acute exposure to oxidative stress in cell culture (16,29), and knockout of PSMB8 produces increased protein oxidation and decreased oxidative stress resistance in laboratory mice (29,30). Our results show that immunoproteasome levels, as measured by PSMB8, are significantly higher in fibroblasts from longer-lived primates than in cells from shorter-lived primates.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…jci.org Volume 125 Number 5 May 2015 oxidized proteins. All 3 immunoproteasome-specific subunits are upregulated under acute exposure to oxidative stress in cell culture (16,29), and knockout of PSMB8 produces increased protein oxidation and decreased oxidative stress resistance in laboratory mice (29,30). Our results show that immunoproteasome levels, as measured by PSMB8, are significantly higher in fibroblasts from longer-lived primates than in cells from shorter-lived primates.…”
Section: Discussionmentioning
confidence: 64%
“…The immunoproteasome has been reported to play an important role both in degradation of oxidized proteins (16,29,30) and in generation of peptides for MHC class I antigen presentation (31,32). We wished to determine whether the increase in immunoproteasome in cells of longer-lived primate species was accompanied by an increase in other aspects of MHC class I antigen presentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that proteasomes containing immuno-subunits have a higher capacity to degrade oxidized proteins than standard-proteasomes . Therefore, the age-dependent increment in intermediate-type and immuno-proteasomes might belong to those cellular mechanisms aimed to balance the consequences of the impaired antioxidative capacity in aging liver (Hussong et al 2010;Suh et al 2004;Stio et al 1994). Since an age-related increase in immuno-subunits was also observed in other tissues, e.g., in skeletal muscle (Husom et al 2004) and brain (Gavilan et al 2009;Mishto et al 2006), we suggest that part of the mechanism to keep up proteostasis during aging is the formation of immunoproteasomes (Mishto et al 2003).…”
Section: Discussionmentioning
confidence: 81%
“…The immunoproteasome is generally expressed in very small amounts in all cells, with the exception of cells from the immune system. However, it can be significantly upregulated through factors like gamma interferon or oxidative stress (23,24). In the immunoproteasome, the subunits ␤1, ␤2, and ␤5 are replaced by the catalytic subunits ␤1i (LMP2, PSMB9), ␤2i (MECL-1, PSMB10), and ␤5i (LMP7, PSMB8), respectively (25)(26)(27).…”
mentioning
confidence: 99%